18F-FDG PET/CT in an Atypical Case of Relapsed IgG4-Related Disease Presenting as Inflammatory Pseudotumor in Gall Bladder Fossa With Extensive Disease Involvement. (October 2018) - Vadi, Shelvin Kumar; Kumar, Rajender; Mittal, Bhagwant Rai; Parihar, Ashwin Singh; Singh, Harmandeep; Singh, Shashank; Rana, Surinder
Abstract : Abstract: Immunoglobulin G4–related disease (IgG4-RD) with multisystem involvement is known to mimic various malignancies and can be diagnosed with high clinical suspicion. We hereby report an atypical case of IgG4-RD, who presented as an inflammatory pseudotumor resembling gall bladder malignancy with hepatic, omental, and subcutaneous involvement. The characteristic tracer uptake pattern described on FDG PET/CT may not be always present in IgG4-RD, especially in the setting of postabdominal surgery. FDG PET/CT revealed the disease progression despite glucocorticoids and aided in response evaluation after second-line drug, rituximab.